Penghambatan Aktivitas Enzim α-Glukosidase oleh Ekstrak Etanol Terstandar Daun Abelmoschus manihot (L.) Medik - Prasetiyo, Andri; Winarti, Wiwi; Agustia, Rini (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
People have long utilised the leaves of the red gedi, Abelmoschus manihot (L.) Medik is an anti-diabetic medication. The study’s objectives were to classify chemical constituent groups, assess extract quality, and evaluate the activity of α-glucosidase enzyme inhibitors. The extraction method employed kinetic maceration with a 70% ethanol solvent, identification was accomplished through phytochemical screening, a quality determination was based on both specific and non-specific parameters, and α-glucosidase inhibition was used in an in vitro antidiabetic activity test. Flavonoids, alkaloids, saponins, steroids, and triterpenoids were found in the phytochemical screening test results. The results of the quality parameter test obtained viscous extract, blackish green color, 70.58% water soluble extract, 49.46% ethanol soluble extract, 7.82% loss on drying, 4.19% water content, total ash content 6.97%, acid insoluble ash content 0.60%, water-soluble ash content 5.64%, residual solvent 0.76%, heavy metal content Pb 1.35 mg/kg, Cd 0.06 mg/kg, plate number total ≤10 colonies/g, yeast plate number 20.1995 colonies/g and total flavonoid content 1.20%. The α-glucosidase enzyme inhibitory activity test from the extract and acarbose (positive controls) obtained IC50 values of 81.84 μg/mL and 42.6 μg/mL, respectively. In conclusion, the α-glucosidase enzyme may be inhibited by the ethanolic extract of A. manihot (L.) Medik leaves.